PROFESIONALISME GURU PAUD DI TK KASIH IBU PADANG: ANALISIS MULTIDIMENSIONAL BERBASIS KERANGKA GLOBAL MENUJU PENGEMBANGAN PROFESIONAL BERKELANJUTAN - Delfi Eliza; Wiwit April Mardianti; Azmi Indah Hatic; Elya Nora (STAI Nurul Falah Airmolek, 2026)
Teacher professionalism is a key determinant in the quality of early childhood education (PAUD). However, studies that integrate the framework of sustainable professional development with the reality of implementation in community-based private early childhood education institutions in Indonesia are still limited. This study aims to analyze the professional profile of teachers at Kasih Ibu Padang Kindergarten through four dimensions of competence, namely pedagogical, personality, social, and professional, as well as identify their supporting and inhibiting factors in the context of 21st century learning. This study uses a qualitative approach with a single case study design. Data were collected through participatory observation, in-depth interviews with teachers and principals, as well as document analysis and parent interviews, then analyzed using an interactive analysis model. The results of the study show that there is a pattern of uneven professionalism, where personality and social-emotional competencies are relatively strong, while pedagogic and professional competencies still need strengthening, especially in technology integration, the application of innovative learning approaches, and the use of authentic assessments. The root of the problem lies in the absence of a planned, systematic, and needs-based system of sustainable professional development. On the other hand, the instructional leadership of the principal and the culture of collaboration between teachers are strategic factors that have the potential to encourage the improvement of teacher professionalism. These findings affirm the importance of strengthening a collaborative, coaching based, and medium-term sustainable professional development system in improving the quality of early childhood education teachers in Indonesia.